Underexplored Connections Between Diabetes, Hypomanic States and Insecure Attachment - Bogdanova D; Maes M; Stoyanov D (Psychology Research and Behavior Management)
Diana Bogdanova,1 Michael Maes,2– 8 Drozdstoj Stoyanov6– 8 1Clinical Psychologist at Center for Psychological Support – PSY HEALTH, Sofia, Bulgaria; 2Sichuan Provincial Center for Mental Health, Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, 610072, People’s Republic of China; 3Key Laboratory of Psychosomatic Medicine, Chinese Academy of Medical Sciences, Chengdu, 610072, People’s Republic of China; 4Department of Psychiatry, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 5Kyung Hee University, Seoul, 02447, Korea; 6Department of Psychiatry and Medical Psychology, Medical University of Plovdiv, Plovdiv, Bulgaria; 7Research Institute, Medical University of Plovdiv, Plovdiv, Bulgaria; 8Research and Innovation Program for the Development of MU – PLOVDIV – (SRIPD- MUP), Creation of a Network of Research Higher Schools, National Plan for Recovery and Sustainability, European Union– NextGenerationEU, Plovdiv, BulgariaCorrespondence: Diana Bogdanova, Clinical psychologist at Center for Psychological Support – PSY HEALTH, Sofia, Bulgaria, Email bogdanovadidi@gmail.comAbstract: Diabetes, dopamine, attachment style disorders, and hypomania share complex interrelations involving neuroinflammation, dysfunction in brain networks (DMN, CEN, SAL), and emotional regulation. Both Type 1 and Type 2 diabetes induce cognitive and structural changes in the brain through mechanisms such as hyperglycemia, insulin resistance, and chronic inflammation. These processes can affect the dopaminergic system, which plays a pivotal role in motivation, emotional regulation, and the manifestation of hypomania. Dopamine is directly linked to attachment styles, with disturbances in this system increasing vulnerability to emotional disorders, including bipolar disorder and schizophrenia. Hypomania, a hallmark of the bipolar spectrum, is associated with dopaminergic imbalances, often observed in diabetes.Keywords: diabetes – type 1 and type 2, dopamine, attachment style, hypomania, mania, bipolar disorder